Optical mapping of site-directed cleavages on single DNA molecules by the RecA-assisted restriction endonuclease technique. - Wang, Y K (1995)
Fluorescence in situ hybridization (FISH) resolution has advanced because newer techniques use increasingly decondensed chromatin. FISH cannot analyze restriction enzyme cutting sites due to limitations of the hybridization and detection technologies. The RecA-assisted restriction endonuclease (RARE) technique cleaves chromosomal DNA at a single EcoRI site within a given gene or selected sequence. We recently described a mapping technique, optical mapping, which uses fluorescence microscopy to produce high-resolution restriction maps rapidly by directly imaging restriction digestion cleavage events occurring on single deproteinized DNA molecules. Ordered maps are then constructed by noting fragment order and size, using several optically based techniques. Since we also wanted to map arbitrary sequences and gene locations, we combined RARE with optical mapping to produce site-specific visible EcoRI restriction cleavage sites on single DNA molecules. Here we describe this combined method, named optical RARE, and its initial application to mapping gene locations on yeast chromosomes.